RECOMMENDATIONS ON DIAGNOSTICS AND TACTICS OF MANAGEMENT OF NIEMANN-PICK DISEASE, TYPE C - L. M. Kuzenkova; L. S. Namazova-Baranova; A. K. Gevorkyan; T. V. Podkletnova; A. M. Mamedyarov (Union of pediatricians of Russia, 2012)
Niemann-Pick disease, type C (NP-C), is a rare hereditary neurovisceral disease caused by mutations in either the NPC1 gene (in 95% of cases) or the NPC2 gene (ca. 5% of cases) which lead to the intracellular lipid transport malfunction and accumulation of cholesterol and glycosphingolipids in brain and other tissues. Characteristic neurological manifestations of NP-C include saccadic eye movement abnormalities or vertical supranuclear gaze palsy, cerebellar manifestations (ataxia, dystonia/dysmetria, dysarthria and dysphagia) and gelastic cataplexy. Epileptic seizures are common in affected patients. The onset of neurological and psychiatric symptoms is considered to occur in childhood, although at present the disease is diagnosed in adulthood in an increasing number of cases due to its late onset. Categorization of patients according to the age at onset of neurological manifestations (antenatal/perinatal, infantile, late infantile, juvenile and adolescent/adult onset) may be useful for the evaluation of disease course and treatment response. The first international guidelines for the clinical management of NP-C in children and adults were published in 2009. Since then a significant amount of data on epidemiology, detection/diagnosis, and treatment of NP-C has been acquired. This publication gives the shared vision of experts in diagnosis and treatment of NP-C elaborated in the course of the regular conference in Paris (France) in September 2011. This article gives updates to the original guidelines, supplements to detection, diagnostics, potentially new methods of the disease progression monitoring and also to the reevaluation of goals of the specific therapy using miglustat.